Penerapan Model Pembelajaran Kausalitik Dalam Meningkatkan Kreativitas Peserta Didik - Imam Al Anshori; Joni Rokhmat; I Wayan Gunada (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This study aims to determine the effect of causal learning models on the creativity of class X students of MAN 2 Mataram academic year 2018/2019. The type of research used was quasi-experimental design with untreated control group design with pretest-and posttest. The population in this study were all students of class X MIA MAN 2 Mataram. The research sample was taken by using purposive sampling technique, so that students of class X MIA 6 were selected as many as 33 people as the experimental class and the X MIA 5 class as many as 34 people as the control class. The experimental class was given treatment in the form of causal learning models and control classes using conventional learning. The instrument used to measure the creativity of students in the form of a description test as many as 6 items. The research hypothesis was tested using the t-test with a significance level of 5%. The results of the t-test obtain a t-count value of 5.02 smaller than t_table which is equal to 2.00 (H0 is rejected and Ha is accepted). So it can be concluded that there is the influence of causal learning models on the creativity of students. This result can be proven by the N-gain test, where there is an increase in creativity by 37% for the experimental class and the control class by 19% with the medium category.